Crime prevention through environmental design principles in residential areas in Abuja, Nigeria - Alexander, Amando (2012)
Due to development pressure, disregard for proper planning for urban growth, and inefficient justice systems, residential areas in Abuja, Nigeria face serious crime problems. Burglaries and assault are among criminal activities that are common in these residential areas. The result of these consistent criminal activities is the creation of prison-like enclaves and fortresses means for residents to protect themselves. This in turn caused ad hoc in urban fabric, disharmony of the city facade, affecting social cohesion and interaction. Crime prevention through environmental design which will be referred to as CPTED in this thesis refers to the development of defensible space through the belief that the physical environment can be manipulated to influence behavior to reduce crime. CPTED is the basis of the design for safer living environment. An array of works from the 70’s up to date have described principles that lead to the effectiveness and success of CPTED programs, and these have been successfully implemented in many countries around the world (United States,Brazil, South America). This study explores the availability of principles of CPTED in present residential areas in Nigeria and how far this principle has been implemented in the selected study sites. The methodology includes extensive literature search, non-participant observation and survey on purposefully selected residential sites in Abuja comprising of two gated and two non-gated communities with equal distances from the city center. In addition, semi-structured interview of four experts, two architects and two planners were also conducted. This research explores whether or not CPTED principles can be applied in these areas as it has been stated that the success of any CPTED program depends solely on the residents to benefit from the program. This means that residents have to support all the four (4) CPTED principles identified in this research (Territoriality, Natural Surveillance, Social interaction, and Image and Milieu) for the program to succeed. Findings from this study showed that the residents in the selected sites support three of the four CPTED principles. Those in the gated communities revealed higher support than those in the non-gated communities. This indicates that crime could be controlled through CPTED in the residential areas in Abuja, Nigeria. This research suggests that missing principle - Social Interaction needs to be established and stressed to ensure the ultimate success of CPTED implementation to prevent crime in residential areas. The results from the research can be used by urban managers, urban designers and planners as well as architects to improve residential design to reduce criminal activities and also to improve good design and encourage social interaction amongst residents to create sustainable and safe cities